Abnormal Peripheral Neutrophil Transcriptome in Newly Diagnosed Type 2 Diabetes Patients - Qiuqiu Lin; Wenzhi Zhou; Yanfei Wang; Juan Huang; Xiaoyan Hui; Zhiguang Zhou; Yang Xiao (Journal of Diabetes Research)
Aim. There are increasing evidence demonstrating that neutrophil-mediated inflammation plays a role in the etiology of type 2 diabetes. However, the molecular mechanisms by which neutrophils contribute to type 2 diabetes remain largely unknown. The aim of the present work was to identify possible changes in circulating neutrophils to better elucidate neutrophil involvement in human type 2 diabetes. Methods. Patients newly diagnosed with type 2 diabetes (n=5) and age- and sex-matched healthy controls (n=5) were recruited. Neutrophils were purified from type 2 diabetes patients and controls, and RNA sequencing (RNA-seq) was used for comprehensive transcriptome analysis. Differentially expressed genes (DEGs) were screened, and Gene Ontology (GO) and KEGG pathway enrichment analyses were performed. Real-time polymerase chain reaction (qPCR) was used for validation in external samples of type 2 diabetes patients (n=8) and healthy controls (n=8). Results. Gene expression analysis showed that, compared with neutrophils from healthy controls, there were 1990 upregulated DEGs and 1314 downregulated DEGs in neutrophils from type 2 diabetes patients. GO analysis demonstrated that the DEGs were mainly involved in myeloid leukocyte activation, T cell activation, adaptive immunity, and cytokine production. The top 20 enriched KEGG pathways included the cytokine-cytokine receptor interaction pathway, NF-κB signaling pathway, cell adhesion molecules, and chemokine signaling pathway. Furthermore, qPCR of genes related to neutrophil activation revealed that the expression of SELL, SELP, CXCR1, and S100A8 was significantly increased in neutrophils from type 2 diabetes patients compared with that in neutrophils from controls. Conclusions. Our study reveals an abnormal activation of circulating neutrophils at the transcriptome level in type 2 diabetes patients. These findings suggest a potential involvement of neutrophil dysfunction in the pathologic process of type 2 diabetes and provide insight into potential therapeutic targets for type 2 diabetes.